1990
DOI: 10.1139/z90-016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of filter feeding in Corbicula fluminea (Bivalvia: Corbiculidae)

Abstract: 1990. Dynamics of filter feeding in Corbiculafluminea (Bivalvia: Corbiculidae). Can J. Zool. 68: 115-120. Filtration rates of Corbiculafluminea were measured using 2-pm microspheres from three riverine habitats which differed in ambient suspended particle concentration; rates were measured at particle concentrations spanning the range for the three habitats. Filtration rates were significantly different across the three habitats, and were inversely correlated with the mean ambient suspended particle concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0
7

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 10 publications
5
76
0
7
Order By: Relevance
“…C. fluminea seems to be a very interesting species from an ecotoxicological point of view because it has some appealing characteristics that could justified its use in this kind of studies, namely: i) this species has become a major component of benthic communities in several lotic and lentic habitats in different regions of the world and, thus, it has a wide spatial distribution; ii) it may be found in both pristine and polluted environments iii) nowadays presents a very strong invasive dynamics in rivers, channels and lakes where it reaches very high abundance (Phelps 1994, Sousa et al 2008; iv) this bivalve is easily maintained in the laboratory for several months and may be transplanted into field conditions using caging procedures (Cataldo et al 2001a); v) this species has a great filtration capacity allowing the uptake of large amounts of pollutants, vi) several field studies have shown that C. fluminea is a good bioindicator of heavy metals or other contaminants (Doherty 1990, Inza et al 1997, Cataldo et al 2001b and vii) the size of adults makes possible the dissection and separation of the main organs allowing specific analysis. The combination of all these traits and its ability to bioaccumulate and bioamplify several contaminants make C. fluminea a very convenient model in ecotoxicology (Way et al 1990, Bassack et al 1997, Baudrimont et al 1997aand b, 2003, Inza et al 1997, Narbonne et al 1999, Tran et al 2001, Cataldo et al 2001aand b, Achard et al 2004). Additionally, due to their ubiquitous distribution, this species can serve as a basis of worldwide comparisons of environmental monitoring data in freshwater ecosystems as the same manner as Mytilus spp.…”
Section: Positive Effects Negative Effectsmentioning
confidence: 99%
“…C. fluminea seems to be a very interesting species from an ecotoxicological point of view because it has some appealing characteristics that could justified its use in this kind of studies, namely: i) this species has become a major component of benthic communities in several lotic and lentic habitats in different regions of the world and, thus, it has a wide spatial distribution; ii) it may be found in both pristine and polluted environments iii) nowadays presents a very strong invasive dynamics in rivers, channels and lakes where it reaches very high abundance (Phelps 1994, Sousa et al 2008; iv) this bivalve is easily maintained in the laboratory for several months and may be transplanted into field conditions using caging procedures (Cataldo et al 2001a); v) this species has a great filtration capacity allowing the uptake of large amounts of pollutants, vi) several field studies have shown that C. fluminea is a good bioindicator of heavy metals or other contaminants (Doherty 1990, Inza et al 1997, Cataldo et al 2001b and vii) the size of adults makes possible the dissection and separation of the main organs allowing specific analysis. The combination of all these traits and its ability to bioaccumulate and bioamplify several contaminants make C. fluminea a very convenient model in ecotoxicology (Way et al 1990, Bassack et al 1997, Baudrimont et al 1997aand b, 2003, Inza et al 1997, Narbonne et al 1999, Tran et al 2001, Cataldo et al 2001aand b, Achard et al 2004). Additionally, due to their ubiquitous distribution, this species can serve as a basis of worldwide comparisons of environmental monitoring data in freshwater ecosystems as the same manner as Mytilus spp.…”
Section: Positive Effects Negative Effectsmentioning
confidence: 99%
“…Although diazinon concentrations dissipated from the water column throughout the 26-day exposure, toxicant bioavailability to deployed clams continued. During this study, filter-feeding from the water column, combined with pedalfeeding of sediment organic matter by C. fluminea (Way et al 1990), seemed to have contributed to clam exposure to diazinon during partitioning to plant and sediment organic matter. Pesticide or metabolites bound to sediments contributed to the decreases in growth and ChE activities in deployed clams.…”
Section: Discussionmentioning
confidence: 77%
“…Site conditions experienced by deployed organisms incorporating benthic and aqueous exposure routes better quantified available toxicants through integration of pesticide partitioning and metabolites. Supplementation of filter feeding by deposit feeding, especially in organic rich substrates (Way et al 1990), is expected to increase the bioavailability of pesticides and their metabolites throughout their transformation within a wetland. Deployed organisms offered an evaluation of techniques for quantifying toxic effects in agricultural mitigation areas to incorporate site-specific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Way et al (1990), the upper limit for efficient filter-feeding is 20-25 µm. However, C. fluminea is capable of pedal-feeding, because the cilia at their foot allowing them to collect organic matter from the sediment, and thus diatoms or organic matter larger than 20 µm particle-size can be also consumed by them (Way et al 1990). This kind of deposit-feeding can increase the amount of food supply for C. fluminea, particularly in habitats lacking appropriate concentration of suspended particles.…”
Section: Discussionmentioning
confidence: 99%